Laser Excisional Biopsy of Bleeding Tumor near Newly Erupted Tooth in an 11-Month-Old Patient under General Anesthesia - Amir Mansour Shirani; Parnian Tadayonnezhad; Sarah Arzani; Seyed Omid Kiansadr; Nasser Kaviani (Case Reports in Dentistry)
Pyogenic granuloma (PG) is a well-known tumor-like growth that commonly appears in the gingiva of the oral cavity. This reactive lesion can develop in response to local irritation, chronic low-grade trauma, long-term low-grade infection, or hormonal imbalances. PG is more frequently observed in individuals during their second and third decades of life, although it can occur at any age. It is more prevalent in young females than males, but on rare occasions, it can be found in children, even infants. Several treatment options exist for PG lesions, which apply after a final diagnosis specified by biopsy and histopathological investigations. Surgical excision is the most common treatment choice for PG lesions. However, comparisons between laser therapy and surgical excision have shown numerous advantages for laser treatment, making it a preferred option for soft tissue lesions. Laser excision offers benefits such as precise and deep incisions, preservation of sterile conditions, improved hemostasis, avoidance of sutures, and less invasive procedures resulting in reduced intra- and postoperative discomfort, pain, and bleeding. This report is aimed at presenting a case of an 11-month-old infant with a gradually growing pyogenic granuloma (PG) lesion that appeared in the palate behind the upper left first deciduous tooth, with a duration of approximately 2 months. The parents reported a history of bleeding associated with the lesion, which emerged after the eruption of the mandibular tooth. An excisional biopsy was done by the application of an 810 nm diode laser under general anesthesia, and the specimen was evaluated by a pathologist. No posttreatment complications or relapses were observed in this case.